2006
DOI: 10.1007/s00359-005-0091-4
|View full text |Cite
|
Sign up to set email alerts
|

Associative visual learning, color discrimination, and chromatic adaptation in the harnessed honeybee Apis mellifera L.

Abstract: We studied associative visual learning in harnessed honeybees trained with monochromatic lights associated with a reward of sucrose solution delivered to the antennae and proboscis, to elicit the proboscis extension reflex (PER). We demonstrated five properties of visual learning under these conditions. First, antennae deprivation significantly increased visual acquisition, suggesting that sensory input from the antennae interferes with visual learning. Second, covering the compound eyes with silver paste sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(105 citation statements)
references
References 47 publications
5
97
2
1
Order By: Relevance
“…Typically 3-5 trials were used (Menzel, 1999;Hori et al, 2006;Niggebrügge et al, 2009). This can lead to long-term effects within 2min if the trials follow each other quickly (Menzel and Müller, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Typically 3-5 trials were used (Menzel, 1999;Hori et al, 2006;Niggebrügge et al, 2009). This can lead to long-term effects within 2min if the trials follow each other quickly (Menzel and Müller, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…A damaged animal will probably be less responsive than an intact animal. The low acquisition rates observed in antennae-deprived bees despite long conditioning procedures (Hori et al 2006(Hori et al , 2007 may be related to this fact. Indeed, it has been recently shown that antennae deprivation reduces sucrose responsiveness when measured through tarsal stimulation (de Brito Sanchez et al 2008), probably leading to a reduction of US value and of acquisition and retention performances.…”
Section: The Originsmentioning
confidence: 99%
“…6 Kuwabara reported that the proboscis extension response of immobilized honeybees could be conditioned using colored lights as CS and sucrose solution delivered to the tarsi as US (Kuwabara 1957). However, Kuwabara's work did not receive broad attention as shown by the fact that almost 50 years passed before other researchers published results on honeybee visual conditioning using Kuwabara's method (Hori et al 2006(Hori et al , 2007. This lack of popularity was probably due to the fact that Kuwabara's results could not be reproduced for many years.…”
Section: The Originsmentioning
confidence: 99%
See 2 more Smart Citations